Pengaruh Kecerdasan Emosional, Etos Kerja, Iklim Organisasi Dan Tunjangan Kinerja Terhadap Kinerja POLRES Kota Metro - Permadi, Elvin; Suwarto, Suwarto (Universitas Muhammadiyah Metro, 2021)
ABSTRACT Permadi, Elvin. 2021. The Influence of Emotional Intelligence, Work Ethic, Organizational Climate and Performance Benefits on the Performance of Metro City Police. Essay. Management Study Program, Muhammadiyah Metro University. Advisors: (1) H. Suryadi, S.E., M.M., Advisors (2) H. Suwarto, S.E., M.M. Keywords: Emotional Intelligence, Work Ethic, Organizational Climate and Performance Benefits on the Performance of Metro City Police The Metro City Police as law enforcers in the Metro City area have an obligation to eradicate crime and create comfort for citizens. The role of human resources is the basic capital in determining whether a person's performance is good or bad. There are several factors that are very influential in the performance of police personnel, namely emotional intelligence, work ethic, organizational climate and personnel performance benefits. The formulation of the problem in this study are 1) Is there an effect of emotional intelligence on the performance of the Metro City Police ?, 2) Is there an effect of work ethic on the performance of the Metro City Police ?, 3) Is there an influence of organizational climate on the performance of the Metro City Police ?, 4) Is there an effect of the performance allowance on the performance of the Metro City Police? Is there an effect of emotional intelligence, work ethic, organizational climate and performance allowances jointly on the performance of the Metro City Police? This research was conducted at the Metro City Police. The sampling technique used Accidental Sampling to 85 respondents, namely the Metro City Police. The analysis technique in this study uses multiple linear regression tests with the help of the SPSS version 21 application. From the results of the study it can be concluded that there is no significant effect of emotional intelligence on the performance of the Metro City Police. Police personnel do not have good emotional intelligence so that they have not been able to improve the performance of the Metro City Police. There is a significant effect of work ethic on the performance of the Metro City Police. The work ethic of the personnel so far has been good and has been able to improve their performance optimally. There is a significant influence of organizational climate on the performance of the Metro City Police. The organizational climate in the Metro City Police has been created in a conducive way and makes personnel comfortable so as to improve their performance. There is no significant effect of performance allowances on the performance of the Metro City Police. The performance allowance given to personnel is still not enough to arouse the enthusiasm of the personnel to improve their performance. There is a significant effect of emotional intelligence, work ethic, organizational climate and performance allowances on the performance of the Metro City Police.